PENGARUH BAURAN PEMASARAN (MARKETING MIX) TERHADAP PENINGKATAN JUMLAH CALON JAMAAH UMRAH DI PT. BIMALYNDO HAJAR ASWAD KOTA BUKITTINGGI - Muhammad Ikram Suhardi; Zuwardi (Adisam Publisher, 2025)
This article discusses the influence of the marketing mix (marketing mix) on increasing the number of prospective Umrah pilgrims at PT. Bilmalyndo Hajar Aswad, City of Bukittinggi, the main problem raised in this article is the lack of interaction between employees of the Umrah travel service provider, namely PT. Bilmalyndo Hajar Aswad for prospective service users who have not used Umrah travel services and there is no increase in the number of prospective Umrah pilgrims using tour travel services. The purpose of this study was to determine the effect of the marketing mix on increasing the number of prospective Umrah pilgrims and to find out the efforts made by PT. Bimalyndo in increasing the number of prospective pilgrims. This research is a quantitative research, which can be interpreted as a method based on the philosophy of positivism, used to examine certain populations or samples. The results showed that the multiple linear regression test obtained a constant value of 1.662, the regression coefficient on the Product variable was 0.201/20.1%, Promotion was 0.307/30.7%, Price was 0.351/35.1%, Place was 0.269/26.9%. Process 0.419/41.9%, Human 0.360/36%, and Physical Evidence 0.314/31.4%. This shows that if every 1% increase in the independent variable, it will affect the increase in Umrah Pilgrims Candidates by the value of the regression coefficient. For the test results the Coefficient of Determination (R2) is 78.1%, there are still other variables that can influence the increase in the number of prospective Umrah pilgrims by 21.9%. This means that this research can still be developed and studied to completion in order to get the effect of the overall value on the Increase in the Number of Prospective Jama'ah. PT. Bimalyndo can analyze more deeply regarding opportunities and steps that must be taken to attract customers by using the marketing mix reference theory in the service sector so that his efforts to increase the number of Umrah pilgrims in his company can be achieved.